History and conservation of wild and cultivated plant diversity in Uganda: forest species and banana varieties as case studies - Hamilton, A.; Karamura, D.; Kakudidi, E. (Elsevier, 2016)
The history of wild and cultivated plant diversity in Uganda is reviewed, taking forest species and bananas as examples. Palynological research into past human influences on forests is reassessed. The evidence suggests that crops were first introduced into the country at about 1000 BCE, farming communities practicing slash and burn agriculture started to significantly influence the floristic composition of forests during the 1st millennium BCE and there was a major episode of forest reduction at about 1000 CE related to socio-economic change. Bananas were probably introduced in the early centuries CE. The colonial era from 1894 saw the introduction of new concepts of land ownership and the establishment of forest reserves and agricultural stations. Forests and banana diversity are currently under threat, Uganda having a very high rate of deforestation and endemic banana varieties proving susceptible to introduced pests and diseases. It is suggested that, under these circumstances, conservationists take an opportunistic approach to field engagement, making use of favourable local conditions as they arise. Partnerships should be sought with elements of society concerned with sustainable use, provision of ecosystem services and cultural survival to widen the social base of plant conservation. International organisations involved in conservation of plant genetic resources and wild plant species should collaborate with one another to develop the conceptual basis of plant conservation, to make it more relevant to countries like Uganda.